Novel diagnostic approaches and biological therapeutics for intrinsic asthma - Vennera, María del Carmen (Dove Medical Press, 2014)
Intrinsic asthma has been considered as a specific disease entity for a long time, although many controversies have emerged in relation to this concept. Of note, not finding specific allergen sensitization in an asthmatic patient neither excludes an allergic component nor the essential role that immunoglobulin E may play in asthma. The diagnostic approach should be similar in any patient suspected to have asthma. The atopic status is one among many other questions. Omalizumab, the only monoclonal anti-immunoglobulin E antibody commercialized for asthma, should be tried in patients with uncontrolled severe asthma independent of their atopic status.